De-novo assembly and comparative analysis of the complete mitogenome of traditional Chinese medicine Strobilanthes sarcorrhiza - Yujie Shi; Ping Li; Jian Sun; Meixin Li; Jingyong Jiang; Yue Xin; Zhen Chen; Wei Zeng (BMC Plant Biology)
Abstract Background Strobilanthes sarcorrhiza is a traditional medicinal plant known for its heat-clearing and kidney-nourishing properties. While its plastid genome has been reported, there is a scarcity of genetic information regarding its mitogenome, leading to unclear phylogenetic relationships. We sequenced and assembled the complete its mitogenome and conducted a series of genetic analyses in conjunction with the plastid genome to gain a better understanding of the species’ genetic background. Results The mitogenome comprised a linear structure spanning 617,134 bp. It included 35 protein-coding genes (PCGs), 19 transfer RNAs (tRNAs), and 3 ribosomal RNAs (rRNAs) that have been annotated. Additionally, 122 simple sequence repeats (SSRs) and 25 tandem repeats were identified. A total of 1,482 pairs of dispersed repeats were detected, which account for 17.58% of the entire mitogenome. Furthermore, 37 migration fragments between the mitochondrial and plastid genomes were discovered, consisting of 5 complete PCGs, 7 tRNAs, and 1 rRNA. Based on the analysis of 38 mitogenomes and 46 plastid genomes, the evolutionary relationship and phylogenetic position of S. sarcorrhiza were elucidated. Conclusions This study has, for the first time, provided insights into the mitochondrial genomic characteristics of S. sarcorrhiza and clarified its phylogenetic position. These findings offered significant insights for the future identification and classification of this genus, as well as for the genetic breeding of medicinal plants.